Rapid life-history evolution reinforces competitive asymmetry between invasive and resident species - Chapuis, Elodie; Jarne, Philippe; David, Patrice (Peer Community Journal)

(untitled)
Biological invasions by phylogenetically and ecologically similar competitors pose an evolutionary challenge to native species. Cases of character displacement following invasions suggest that they can respond to this challenge by shifting their traits. However, the actual impact of such shifts on competition are seldom studied. Here, we study competition between two freshwater snails from Guadeloupe (French Antilles), the native Aplexa marmorata and the introduced Physa acuta. The former has responded to invasion by rapid life-history evolution towards earlier maturity, higher fecundity and higher juvenile survival, traits that might favor rapid population growth in a noncompetitive context, but not necessarily in a competitive one. We here observe negative impacts of competition by both species on each other, though P. acuta is dominant and over generations largely displaces A. marmorata from co-cultures. In addition, our experiments suggest that A. marmorata populations having experienced competition by P. acuta for sufficient time in nature, have evolved to become even less tolerant to it. Though apparently paradoxical, this result supports the hypothesis that rapid life-history evolution has allowed A. marmorata not to resist competition, but to avoid it by increasing its specialization into the colonizer lifestyle previously documented by long-term field surveys. This example illustrates how evolution, in accordance with metacommunity coexistence theory, sometimes takes other ways than specialization into distinct types of resources or habitats to ensure coexistence between related species inhabiting the same landscape.